(untitled) (Journal of the College of Basic Education, 2025)
The research aimed to investigate the impact of the diagnostic evaluation strategy on learning football scoring skills among students at Al-Mahmoudiya Scientific Preparatory School for Boys, affiliated with the Second Al-Karkh Directorate . The researcher hypothesized that there are statistically significant differences between the pre-test and post-test results of the experimental and control groups ، in favor of the post-test . The researcher used the experimental method with pre- and post-tests . The study sample consisted of fifth-grade science students, totaling (62) students ، divided into experimental and control groups . The post-test results between the two groups showed a positive effect on learning football scoring skills. Additionally ، the researcher recommended the importance of leveraging the advantages of the diagnostic evaluation strategy for learning football skills in particular and sports skills in general .